2019
DOI: 10.1111/aogs.13775
|View full text |Cite
|
Sign up to set email alerts
|

Non‐obstetric abdominal surgery during pregnancy and birth outcomes: A Danish registry‐based cohort study

Abstract: Introduction Surgery during pregnancy may increase the risk of adverse birth outcomes. In this nationwide registry‐based cohort study including women aged 15‐54 years with singleton birth or miscarriage, we examined the association between non‐obstetric abdominal surgery during pregnancy and the birth outcomes small‐for‐gestational‐age (SGA), preterm birth, and miscarriage. Material and methods The study used data on births or miscarriages from the large national Danish registries in 1997‐2015. We calculated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…However, the decisions regarding timing, approach and the appropriateness of surgery are often challenging. There have been few published reports on IBD surgery during pregnancy most likely due to low frequency and underreporting [7][8][9][10][11] . In this respect, data on the outcomes of surgery due to IBD in pregnant patients are scarce, and primarily date back more than 3 decades ago predating the use of biologic therapy, minimally invasive surgery and current perioperative management and support 7 .…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the decisions regarding timing, approach and the appropriateness of surgery are often challenging. There have been few published reports on IBD surgery during pregnancy most likely due to low frequency and underreporting [7][8][9][10][11] . In this respect, data on the outcomes of surgery due to IBD in pregnant patients are scarce, and primarily date back more than 3 decades ago predating the use of biologic therapy, minimally invasive surgery and current perioperative management and support 7 .…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…In general, it has been reported that both sigmoidoscopy and colonoscopy are of low risk in pregnant IBD patients and can guide the decision making process in a high proportion of patients [19][20][21] . Some authors have suggested that surgery is of lowest risk when undertaken during the 2 nd trimester there are higher risks of miscarriage in the 1 st trimester and increased risks of maternal/foetal morbidity and mortality during the 3 rd trimester 7,11 . Nevertheless, and despite With respect to the surgical approach, a minimally invasive approach is advocated by a number of authors from extrapolation from general surgical procedures during pregnancy or from surgery in non-pregnant IBD patients 7,[22][23][24] .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Women with obstruction, abscess, refractory colitis, hemorrhage, and appendicitis, among other medical conditions, may require more emergent surgery during pregnancy. A study using the Danish national registries of 1,202,870 pregnancies, including 4490 (0.4%) women who had non-obstetric abdominal surgery during pregnancy, showed increased risk of small for gestational age, very preterm births, preterm birth, and miscarriage among women who underwent surgery during pregnancy; the greatest risk for these outcomes occurred within 14 days after surgery [53]. The risk of miscarriage decreased with time after surgery and, after 2 weeks, approached that of pregnancies without surgery.…”
Section: Surgical Management Of Complicated Ibd During Pregnancymentioning
confidence: 99%
“…Acute appendicitis is the most common non-obstetric surgical emergency during pregnancy, followed by cholecystitis, pancreatitis, and bowel obstruction [ 3 , 4 ]. In addition, acute appendicitis is the most common cause of non-obstetric surgical intervention performed during pregnancy, accounting for 25% of non-obstetric surgical interventions during pregnancy [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%